Fabrication and varification of porous silicon nanostructures/ zinc oxide nanostructures as a capacitive chemical sensors by electrochemical impedance method / Mohd Husairi Fadzilah Suhaimi - Fadzilah Suhaimi, Mohd Husairi (Institute of Graduate Studies, UiTM, 2015)
In this study, preparation and optimization of ZnO nanostructures on PSiNs for chemical sensor was studied. The PSiNs was prepared by electrochemical etching using p-type, [100] orientation silicon wafer as a based material. The PSiNs samples were prepared by the electrochemical etching with photoassisted at different current density in the range of 15–40 mA/ cm² and etching time at 10–50 minutes. Photoluminescence spectra show blue shift with increasing applied current density that is attributed by PSiNs pillar size. Variations of electrical resistance and capacitance values of PSiNs were measured using EIS. These results indicate that PSiNs prepared at 20 mA/cm² current density and 30 minutes have uniform porous structures with a large demsity of pillars. Furthermore, PSiNs structure influences large values of charge transfer resistance and double layer capacitance, indicating potential application in sensors. The ZnO nanostructures were synthesized on PSiNs substrates using thermal catalytic-free immersion method with Zn(NO₃)₂6H₂O as a precursor and CH₄N₂O as a stabilizers. Three parameters was used to optimized the maximum changes of capacitance on ZnO nanostructures on PSiNs, solution concentration (0.1, 0.2 and 0.3 molar), molarity of CH4N2O (0.05, 0.1, 0.2, 0.4 and 0.6 molar) and immersion time (2, 4, 6, 8 and 10 hour)…